Civil Passions : Moral Sentiment and Democratic Deliberation. - Krause, Sharon R. (Princeton University Press, 2010)
Must we put passions aside when we deliberate about justice? Can we do so? The dominant views of deliberation rightly emphasize the importance of impartiality as a cornerstone of fair decision making, but they wrongly assume that impartiality means being disengaged and passionless. In Civil Passions, Sharon Krause argues that moral and political deliberation must incorporate passions, even as she insists on the value of impartiality. Drawing on resources ranging from Hume's theory of moral sentiment to recent findings in neuroscience, Civil Passions breaks new ground by providing a systematic.